The public’s perception of international climate leadership: insights from the European Union - Tosun, Jale; Mišić, Mile; Schmidt, Nicole (Transformative climates and accountable governance, 2019)
Delegation and accountability are central concepts for analysing political processes. This contribution engages in these debates by examining the public’s perception of climate change in the European Union (EU) and analyses the willingness of European citizens to delegate competences for governing climate change. Drawing on Eurobarometer surveys, we find that respondents in some states show below-average support for the EU’s responsibility in tackling climate change, whereas respondents in other states support very strongly the EU’s involvement in climate policymaking. Moreover, European citizens indeed prefer to diffuse policy competences across different levels, which reveals the EU has a domestic legitimacy to address climate change.
First Online: 26 September 2018
Gesehen am 27.08.2019